Religious guidance services to troubled women in providing legal protection : (A case study at Rumah Perlindungan Remaja Wanita Pertubuhan Kebajikan Darul Anisah Kuantan Pahang, Malaysia) - Hanani, Tengku Atiyah; Samosir, Hasrat Efendi; Kustiawan, Winda (International Journal on Social Science, Economics and Art, 2024)
In this modern era, the phenomenon of adolescents is often exposed to social problems that are increasing day by day. Religious guidance is one of the initiatives used to provide knowledge and assistance regarding religion both physically and spiritually to residents of the Darul Anisah Protection House. With the provision of this assistance, it is hoped that the residents can grow into happy individuals in this world and in the hereafter and can avoid actions that violate shara' law. The purpose of this study is to determine the religious guidance services to troubled women in providing legal protection at Darul Anisah Protection House Kuantan Pahang Malaysia. The research method used in this article is case study qualitative research. Case study research is a form of qualitative research based on human understanding and behavior based on human opinion. Data collection techniques are obtained through observation, interviews, and documentation. Based on the results of the analysis that has been done, the results discussed in this article are about religious guidance services for troubled women by applying Islamic religious principles through religious guidance methods and materials.